INVENTARISASI JENIS TUMBUHAN DURIAN PADA HUTAN KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Yosef Kafaso; Rahmidiyani Rahmidiyani; Warganda Warganda (Jurnal Sains Pertanian Equator, 2019)
INVENTARISASI JENIS TUMBUHAN DURIAN PADA  HUTAN KECAMATAN SEKADAU HILIR KABUPATEN SEKADAUYosef Kafaso1, Rahmidiyani2, Warganda3 1Budidaya; Universitas Tanjungpura2Budidaya; Universitas Tanjungpura3Budidaya; Universitas Tanjungpurae-mail: *1yosefkafaso94@gmail.com ABSTRACTThe aim of this research was to know the variety of Durio plant in Kecamatan Sekadau Hilir, Kabupaten Sekadau. This research was conducted in Seguri forest located at Desa Peniti, Entada forest in Desa Gonis Tekam and Munggu Betung forest in Desa Semabi for three months, started from December 2017 until March 2018, using survey method by exploring all of the Tembawang Seguri forest areas and Tembawang Entada forest. The sampling was done by purposive sampling. The criteria of the mature plants and plant that has been fruitful several times. Based on the result of the research in the field, there are six types of Durian, the six types of Durian are Durio zibethinus, Durio kutejensis, Durio oxleysnus, Durio lanceolatus, Durio lowianus and Durio excelcus. The type of Durio zibethinus Murr was the most widely plant found in Entada,Seguri  and Munggu Betung forest. Durio lanceolatus only found in Entada forest. Durio  lowianus was found in the Entada and Munggu Betung forest and Durio exelcus was found in Seguri and Munggu Betung forest. Generally, the place of Durian plant not really different in each species, based on the vegetation, the condition of environment. The difference was only in the height of the place and habitat, and even it was still in a condition that the durian plant wants to grow. There were no specific species found of Durian in the others location because the trees was cut down by the villagers because of the unpleasant taste of the fruit, the conversion of land functions such as agriculture, house building infrastructure and others, and lack of public awareness of biodiversity conservation.   Keywords: Durian, Durian’s habitat, Kabupaten Sekadau.